Editorial by the Honorary Editor-in-Chief - Editor-in-chief, Honorary (Biomedicine & Healthcare Research, 2025)
With the release of the fourth volume of Biomedicine & Healthcare Research, the official scientific journal of the Faculty of Medicine of Sousse, we are excited to highlight several key milestones that reflect the growth and global recognition of our journal. First, in partnership with the Tunisian DOI Consortium and the National Center for Scientific and Technical Documentation (CNUDST), our journal has successfully obtained a Digital Object Identifier (DOI). This achievement guarantees that each article published is uniquely and permanently identifiable, enhancing its visibility, traceability, and citation within the international research community. In another significant development, Biomedicine & Healthcare Research has been selected by the Union of Arab Scientific Research Councils for support in its indexing on Scopus, one of the world’s most prestigious bibliographic databases. This inclusion will elevate our journal’s global reach and credibility, reinforcing our commitment to upholding the highest standards of scientific excellence. Additionally, our Faculty has achieved ISO 21001:2018 certification, recognizing our dedication to quality management in higher education and scientific research. This certification underscores our ongoing efforts to cultivate innovative and impactful research practices across medical studies, professional programs, and doctoral research. These accomplishments reflect our steadfast commitment to advancing scientific knowledge and expanding our global presence. We are deeply grateful to our partners, authors, and readers for their continued support. As we celebrate the publication of the fourth volume of Biomedicine & Healthcare Research, we invite you to explore its content, which includes seven papers: three original articles and four case reports, contributed by talented biomedical teams from Tunis, Ariana, Nabeul, Sousse, and Sfax. These contributions highlight the excellence of our national research community and showcase the diversity and impact of research in biomedicine and healthcare. We look forward to your continued readership and eagerly anticipate your future contributions to Biomedicine & Healthcare Research. Pr. Mohamed Ben Dhiab